2004
DOI: 10.1023/b:biry.0000022066.38297.8a
|View full text |Cite
|
Sign up to set email alerts
|

pH Dependence of the Efficiency of Binding of Iron Cations to the Donor Side of Photosystem II

Abstract: Light-induced interaction of Fe(II) cations with the donor side of Mn-depleted photosystem II (PS II(-Mn)) results in the binding of iron cations and blocking of the high-affinity (HAZ) Mn-binding site. The pH dependence of the blocking was measured using the diphenylcarbazide/2,6-dichlorophenolindophenol test. The curve of the pH dependence is bell-shaped with pK1 = 5.8 and pK2 = 8.0. The pH dependence of the O2-evolution mediated by PS II membranes is also bell-shaped (pK2 = 7.6). The pH dependence of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Having in mind that Fe(II) is not bound by the native PSII membranes (Table 1) and the depletion of Mn clusters makes the oxidants at the donor side of PSII available for the exogenous electron donors [1], we concluded that the diminished concentration in the light could resulted from Fe(II) oxidation and from binding Fe(III) cations thus produced to the PSII(-Mn) membranes. Indeed, the absence of mononuclear Fe(II)-binding centers in the PSII(-Mn) membranes was confirmed by moessbauer spectrometric data [23]. However, it is plausible that Fe(II) or cations of intermediate valence may be found in polynuclear Fe clusters, same as in iron-sulfur clusters [24].…”
Section: Binding Fe(ii) and Fe(iii) Cations To Psii And Psii(-mn) Memmentioning
confidence: 87%
“…Having in mind that Fe(II) is not bound by the native PSII membranes (Table 1) and the depletion of Mn clusters makes the oxidants at the donor side of PSII available for the exogenous electron donors [1], we concluded that the diminished concentration in the light could resulted from Fe(II) oxidation and from binding Fe(III) cations thus produced to the PSII(-Mn) membranes. Indeed, the absence of mononuclear Fe(II)-binding centers in the PSII(-Mn) membranes was confirmed by moessbauer spectrometric data [23]. However, it is plausible that Fe(II) or cations of intermediate valence may be found in polynuclear Fe clusters, same as in iron-sulfur clusters [24].…”
Section: Binding Fe(ii) and Fe(iii) Cations To Psii And Psii(-mn) Memmentioning
confidence: 87%
“…In general, any pH-dependent binding involves proton uptake/release and therefore causes changes in the protonation states of ionizable groups. The literature is full of examples of experimental data demonstrating pH-dependent binding from ion binding to small peptides [20] or proteins [21], and acid-organic compounds [22], to protein-small molecule [23, 24] and protein-protein binding [2527]. All of these examples demonstrate that protonation states frequently change due to the binding.…”
Section: Introductionmentioning
confidence: 99%